Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Chitosan hydrochloride-gum Arabic-passion fruit seed oil nanoparticle edible coating to control fungal infection and maintain quality parameters of strawberries - Alessandra Silva Araújo; Gerlane Souza de Lima; Ihasmyn dos Santos Nunes; Júlio César Ribeiro de Oliveira Farias de Aguiar; Daniela Maria do Amaral Ferraz Navarro; Natália Ferrão Castelo Branco Melo; Nereide Stela Santos Magalhães; Rodrigo França; Rafaela de Siqueira Ferraz Carvalho; Thayza Christina Montenegro Stamford (Food Control, 2024)

Public perceptions of marine litter and impacts on coastal ecosystem services in Galicia (Spain) - Mariana Herrera; Pablo Pita; Daniela Castelo; C. Marisa R. Almeida; Sandra Ramos; Sebastián Villasante (Marine Policy, 2023)

Identifying sustainability priorities among value chain actors in artisanal common octopus fisheries - Gillian B. Ainsworth; Pablo Pita; Cristina Pita; Katina Roumbedakis; Graham J. Pierce; Catherine Longo; Gregory Verutes; Tereza Fonseca; Daniela Castelo; Carlos Montero-Castaño; Julio Valeiras; Francisco Rocha; et al. (Reviews in Fish Biology and Fisheries, 2023)
The United Nations (UN) Decade of Ocean Science highlights a need to improve the way in which scientific results effectively inform action and policies regarding the ocean. Our research contributes to achieving this goal by identifying practical actions, barriers, stakeholder contributions and resources required to increase the sustainability of activities carried out in the context of artisanal fisheries to meet UN Sustainable Development Goals (SDG) and International Year of Artisanal Fisheries and Aquaculture (IYAFA) Global Action Plan (GAP) Pillar targets. We conducted a novel ‘social value chain analysis’ via a participatory workshop to elicit perspectives of value chain actors and fisheries stakeholders associated with two Spanish artisanal common octopus ( Octopus vulgaris ) fisheries (western Asturias—Marine Stewardship Council [MSC] certified, and Galicia—non-MSC certified) about their priorities regarding sustainable octopus production and commercialization. Our adapted Rapfish sustainability framework emphasised the importance of economic, environmental, ethical, institutional, social, and technological indicators to different actors across the value chain. We mapped participants’ shared sustainability priorities (e.g. integrated fisheries management, knowledge-based management, product traceability) to six Rapfish indicators, seven IYAFA Pillars and twelve SDGs to reveal how our results can inform ocean policy and actions. This identified how certification incentives and other cooperative approaches can facilitate environmental, economic and social sustainability (e.g. value-added products, price premiums for producers, gender inclusive organisations); support IYAFA priority outcomes (raised awareness, strengthened science-policy interface, empowered stakeholders, partnerships); and help to achieve UN SDG targets (e.g. SDG 14.b, SDG 17.17). The results can inform actors, stakeholders and policymakers about how different actors contribute to efforts to achieve the SDGs and how to manage priorities for sustainable actions within artisanal fisheries and their value chains. We recommend inclusive and equitable participatory knowledge transfer and governance platforms as part of the UN Decade of Ocean Science and beyond where participants can create theories of change towards sustainability involving the development of multi-sectoral ocean policies framed at the level of the value chain and supported by appropriate governance structures. Graphical Abstract

Diabetic brain or retina? Visual psychophysical performance in diabetic patients in relation to GABA levels in occipital cortex - Mafalda Sanches; Sulaiman I Abuhaiba; Otília C. d’Almeida; Bruno Quendera; Leonor Gomes; Carolina Moreno; Daniela Guelho; Miguel Castelo-Branco (Metabolic Brain Disease, 2017)